Latar Ombo, Fungsi dan Konsep Ruang Publik di Desa Tieng Kabupaten Wonosobo - Heri Hermanto; Achmad Djunaidi; S Sudaryono (Forum Teknik, 2013)
Latar ombo (a wide yard) at Tieng village Dieng Wonsobo has a function as a public area to hold cultural and tradition activities. The research questions are, how latar ombo function and role as public area society and  what concept underline the building of latar ombo at the Tieng village.The research uses phenomenology  by inductive technique. Data by collected by deep interview, the informans are ten peple.Based on inductive analysis about information units, it can be found three themes. Then these were discussed to know the local concepts of public space. The result shows that there are interrelation among latar ombos owned by people at Tieng village so that latar ombo becomes a public area which is needed by society.Keywords:  public space, latar ombo, the concept of  interrelation